The Effect of Gold Prices on The Composite Stock Price Index with Inflation as A Moderating Variable - Marieska Lupikawaty; Novitasari; Angga Nugraha; Vidya Ramadhan Putra Pratama; Riris Lawitta (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study aims to analyze the influence of global gold price fluctuations on the Jakarta Composite Index (JCI), with inflation as a moderating variable. Using portfolio theory and the efficient market hypothesis, this study examines gold as a safe-haven asset and its relationship with the domestic capital market during periods of inflationary pressure. The data used are secondary time series data analyzed using the Moderate Regression Analysis (MRA) method. The results show that gold prices have a significant influence on JCI movements, but the strength of this relationship depends strongly on the inflation rate. Inflation is found to act as a moderating variable, strengthening the shift in investment from the stock market to gold when the currency's purchasing power declines. This research provides strategic implications for investors in diversifying their portfolios and for policymakers in maintaining the stability of the national financial market.